Theatron Rhetorische Kultur in Spätantike und Mittelalter / Rhetorical Culture in Late Antiquity and the Middle Ages - Grünbart, Michael (Millennium-Studien / Millennium Studies, 2012)
This volume presents 22 studies on aspects of rhetorical culture from Late Antiquity to the last years of the Byzantine Empire. Many of them concentrate on the effects and social relevance of the art of public speaking, above all in the Greek speaking world, and particular attention is paid to the performative character of rhetoric. The contributions deal both with individual authors, as well as general phenomena of medieval literature.